A construção das subjetividades femininas em como água para chocolate, de Laura Esquivel - Santos, Jenison Alisson dos (2018)
This dissertation proposes an analysis of the development of the female subjectivities in Como água para chocolate, by Mexican author Laura Esquivel, taking into consideration the gastronomic discourse present throughout the novel. For this purpose, our endeavor contemplates four possibilities of investigation, aiming for a better understanding of said phenomenon: the presence of women’s voices in the process of (re)writing History; the movements of oppression and resistance in the kitchen space; the affect among characters weaved from the gastronomic discourse; and the different standpoints on motherhood. Our theoretical framework encompasses an interdisciplinary study, undergoing Literary Theory and Criticism, History, Historiography, Philosophy and the study on the relation between the culinary rhetoric and literature, something that allows for a more comprehensive and meaningful approach. Our arguments are supported by theoretical principles drawn mainly from Woolf (2014), Sceats (2003), Badinter (1985) e Hutcheon (1987). As a result of the dialogue between the novel and the theoretical framework, we have been able to discuss the ways in which Esquivel constructs a singular narrative, demonstrating inventive capacity, resistance and empowerment of her female characters deriving from the experiences of everyday life, and subverting the expectations of representation of those characters in the literary canon.